Bite’em Cookies / Muhammad Amin Nurrasyid Zul Helmi and Muhammad Azhan Fikri Rozali - Zul Helmi, Muhammad Amin Nurrasyid; Rozali, Muhammad Azhan Fikri (2022)
Bite’em cookies is a brand of homemade dark chocolate cookies established because of passion from the duo bakers. We choose to create a cookies business because people love simple yet delicious snacks that fit for every event. The production of cookies is located in Bukit Sentosa, Rawang, where we only use high quality ingredients. Our mission is to create a tasty dark chocolate cookie in town, homemade! Thus, our vision is to establish a proper business entity such as a bakery in the future. By doing that, our customers will feel comfortable, relaxed and enjoyed. Besides, we also would create various types of cookies gradually in 2 years, so that our customers would have lots of options to find their favorite. The strength of our brand that could be an advantage among the competitors is cheaper price, high-quality ingredients, and advertising. Also, Our business is operated in online and offline mode. The baker for this creation of this masterpiece is Muhammad Amin Nurrasyid and Muhammad Azhan Fikri. Our knowledge and experiences in food and bakery services, combined with connection with the community, will make this business well- known worldwide, and gain endless profit.